The Effect Of Debt Policy, Company Size And Profitability On Company Value In The Industrial Sector On The IDX - octavia, Melanie; Sari, Adila; Natasha Natasha; Purba, Seprianto; An Suci Azzahra (International Journal of Economic Research and Financial Accounting, 2025)
The purpose of the study is to look at the influence of debt policy, company size and profitability on company value in industrial companies listed on the Indonesia Stock Exchange during the 2020-2023 period. This study is a quantitative researcher with a secondary data collection method, the population of this study is 66 companies, sampling is carried out by purposive sampling, and data analysis uses multiple linear regression through SPSS. The results of the study stated that partially debt policy had a positive and significant effect, partially the size of the company had no effect or had a positive and insignificant effect, then partially profitability had a positive and significant effect. And simultaneously debt policy, company size and profitability had a significant effect, by 16.7%.